2018
DOI: 10.1029/2018jd029042
|View full text |Cite
|
Sign up to set email alerts
|

The Clustering of Severe Dust Storm Occurrence in China From 1958 to 2007

Abstract: China is subjected to severe dust storms that deteriorate air quality and cause substantial damages to environment and socioeconomics. Although the annual frequency of severe dust storms in China has been declining since the 1950s, the variability of severe dust storm occurrence in time and space remains inadequately described under the changing climate. Based on the continuous observation at 368 meteorological observation sites across the mainland China over a 50-year period (1958 to 2007), we found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
6
2
Order By: Relevance
“…The two DS types exhibit significant differences in both long term trend and spatial pattern of the occurrences of DS. Although there is a consensus on the decreasing trend of DSs in northern China over the past decades (Guo et al, 2018;Qian et al, 2002;Zhu et al, 2008), our findings suggest that T1 DSs induced by Mongolian cyclone has no trend, and hence T2 DSs are primarily responsible for the declining trend of DSs in northern China. Such conclusion is supported by Zhu et al (2008), who applied the Empirical Orthogonal Function analysis to the spring DS frequency during 1954-2007 and found no significant trend for the second leading mode (similar to our T1 DS characterized by high DS frequency in the Inner Mongolia).…”
Section: Discussioncontrasting
confidence: 71%
“…The two DS types exhibit significant differences in both long term trend and spatial pattern of the occurrences of DS. Although there is a consensus on the decreasing trend of DSs in northern China over the past decades (Guo et al, 2018;Qian et al, 2002;Zhu et al, 2008), our findings suggest that T1 DSs induced by Mongolian cyclone has no trend, and hence T2 DSs are primarily responsible for the declining trend of DSs in northern China. Such conclusion is supported by Zhu et al (2008), who applied the Empirical Orthogonal Function analysis to the spring DS frequency during 1954-2007 and found no significant trend for the second leading mode (similar to our T1 DS characterized by high DS frequency in the Inner Mongolia).…”
Section: Discussioncontrasting
confidence: 71%
“…Connecting climate trends to natural disasters has become an essential issue of significant scientific and public interest [ 16 , 41 ]. Many previous studies have provided evidence that the increasing number of natural disasters is closely associated with rising temperatures [ 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Che et al [ 14 ] suggested that special attention should be paid to the relationship between earthquakes and the rising soil temperature in the warm permafrost regions on the Tibet Plateau, a primary active seismic zone in China. Taken together, climate-related natural disasters have severely impacted human livelihoods and natural environments around the world [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dust storms are reported and analyzed for many arid and semi‐arid regions on Earth, such as North Africa (e.g., Huneeus et al, ), Arabian Peninsula (e.g., Notaro et al, ), China (e.g., Guo et al, ), Central Asia (e.g., Indoitu et al, ), and Australia (e.g., Gabric et al, ). Severe dust events are usually triggered by large‐scale synoptic controls, as high wind speeds over wide areas are required for their development.…”
Section: Introductionmentioning
confidence: 99%